OC-018 The role of a point of care test (iga/igg-deamidated gliadin peptide) in predicting histological remission in coeliac disease on a gluten free diet. (17th June 2017) - Lau, MS; Mooney, PD; White, WL; Rees, MA; Burden, M; Wong, SH; Sanders, DS
Abstract : Introduction: Coeliac disease (CD) is a chronic inflammatory enteropathy treated with a gluten free diet (GFD). Non adherence can lead to symptoms and complications such as osteoporosis and malabsorption. Moreover, patients with persistent villous atrophy are twice as likely to develop lymphoproliferative malignancies compared to those who achieve mucosal healing. Therefore, the optimal assessment of treatment response is the evaluation of duodenal histology. However, there is little consensus in the UK on routine follow up biopsy. Duodenal biopsy requires a gastroscopy which is invasive and can be poorly tolerated. There is currently no reliable surrogate marker for histological remission in our daily clinical practice. We aimed to assess the role of a finger prick point of care test (POCT), Simtomax (IgA/IgG-deamidated gliadin peptide, Tillotts Pharma, Rheinfelden, Switzerland), in predicting histological remission in CD. Method: We prospectively recruited patients with known CD attending for a gastroscopy with duodenal biopsy for the assessment of histological remission. IgA-endomysial antibodies (EMA), IgA-tissue transglutaminase antibodies (TTG), total IgA levels and the POCT were performed in all patients at endoscopy. Patients also completed a validated GFD adherence questionnaire devised by Biagi et al. which gives a 5 point score (0–4), with the highest score indicating strict dietary adherence. A gastroscopy was performed with quadrantic biopsies taken from the second part of the duodenum and one from the duodenal bulb. We compared all surrogate markers to the gold standard of duodenal histology. Results: A total of 217 (70% female, age range 16–83, median age 53) patients with CD on a GFD (median duration 6 years) were recruited from 2013–2017. Eighty-five (39.2%) patients had persistent villous atrophy. The POCT was the most sensitive surrogate marker for predicting villous atrophy (p=0.0005). Conclusion: Of all clinically available surrogate markers, the POCT was the most sensitive in predicting villous atrophy. The POCT has the additional advantage of convenience being a finger prick test, providing rapid results within 10 min. In combination with clinical and dietetic assessments, the POCT could aid clinical decision making on the necessity of follow-up duodenal biopsy within the same consultation. Disclosure of Interest: M. Lau: None Declared, P. Mooney: None Declared, W. White: None Declared, M. Rees: None Declared, M. Burden: None Declared, S. Wong: None Declared, D. Sanders Conflict with: Professor Sanders has received educational research grants from Dr Schaer (a gluten-free food manufacturer) and Tillotts Pharma (producer of a point of care test for celiac disease) for investigator led studies. Dr Shaer and Tillott's Pharma did not have any input in the study design, access to study data, interpretation of the findings or drafting of the manuscript.